Modulation of Anionic Lipid Bilayers by Specific Interplay of Protons and Calcium Ions - Abhinav; Jurkiewicz, Piotr; Hof, Martin; Allolio, Christoph; Sýkora, Jan (Biomolecules, 2022)
Biomembranes, important building blocks of living organisms, are often exposed to large local fluctuations of pH and ionic strength. To capture changes in the membrane organization under such harsh conditions, we investigated the mobility and hydration of zwitterionic and anionic lipid bilayers upon elevated H3O+ and Ca2+ content by the time-dependent fluorescence shift (TDFS) technique. While the zwitterionic bilayers remain inert to lower pH and increased calcium concentrations, anionic membranes are responsive. Specifically, both bilayers enriched in phosphatidylserine (PS) and phosphatidylglycerol (PG) become dehydrated and rigidified at pH 4.0 compared to at pH 7.0. However, their reaction to the gradual Ca2+ increase in the acidic environment differs. While the PG bilayers exhibit strong rehydration and mild loosening of the carbonyl region, restoring membrane properties to those observed at pH 7.0, the PS bilayers remain dehydrated with minor bilayer stiffening. Molecular dynamics (MD) simulations support the strong binding of H3O+ to both PS and PG. Compared to PS, PG exhibits a weaker binding of Ca2+ also at a low pH.
Keywords: Phosphatidylserines; lipidové dvojvrstvy; headgroup mobility; calcium; vápník; Ions; Molecular Dynamics Simulation; ionty; Lipid Bilayers; proton; time dependent fluorescence shift; Calcium; headgroup organization; lipid hydration; fosfatidylseriny; molecular dynamics; anionic lipids; Laurdan; simulace molekulární dynamiky; Protons; phospholipid bilayer; protony